Taxonomy and the DNA Barcoding Enterprise - Ebach, Malte C. (Zootaxa, 2011)
DNA Barcoding is elusive to many taxonomists. Like the numbers in a barcode, barcoding attempts to link a type specimen with a part of its DNA, most commonly from the mitochondrial Cytochrome c Oxidase subunit I (COI) gene.